Site Resource Inventories – a Missing Link in the Circular City's Information Flow - G. Baganz; G. Baganz; G. Proksch; W. Kloas; W. Kloas; W. Kloas; W. Lorleberg; D. Baganz; G. Staaks; F. Lohrberg (Advances in Geosciences, 2020)
A circular city builds upon the principles of circular economy, which key concepts of reduce, reuse, recycle, and recover lead to a coupling of resources: products and by-products of one production process become the input of another one, often in local vicinity. However, sources, types and available quantities of underutilised resources in cities are currently not well documented. Therefore, there is a missing link in the information flow of the circular city between potential users and site-specific data. To close this gap, this study introduces the concept of a site resource inventory in conjunction with a new information model that can manage the data needed for advancing the circular city. A core taxonomy of terms is established as the foundation for the information model: the circular economy is defined as a network of circular economy entities which are regarded as black boxes and connected by their material and energy inputs and outputs. This study proposes a site resource inventory, which is a collection of infrastructural and building-specific parameters that assess the suitability of urban sites for a specific circular economy entity. An information model is developed to manage the data that allows the entities to effectively organise the allocation and use of resources within the circular city and its material and energy flows. The application of this information model was demonstrated by comparing the demand and availability of required alternative resources (e.g. greywater) at a hypothetical site comprising a commercial aquaponic facility (synergistic coupling of fish and vegetables production) and a residential building. For the implementation of the information model a proposal is made which uses the publicly available geodata infrastructure of OpenStreetMap and adopts its tag system to operationalise the integration of circular economy data by introducing new tags. A site resource inventory has the potential to bring together information needs and it is thus intended to support companies when making their business location decisions or to support local authorities in the planning process.